Cassava mosaic geminiviruses associated with cassava mosaic disease in Rwanda - Sseruwagi, P.; Okao-Okuja, G.; Kalyebi, A.; Muyango, S.; Aggarwal, V.; Legg, James P. (Informa UK Limited, 2005)
Cassava mosaic disease (CMD), and cassava mosaic geminiviruses (CMGs), were investigated in a country-wide survey conducted in six cassava-producing prefectures (administrative regions) of Rwanda in 2001. CMD occurred throughout the country at an average incidence of 30%. Incidence was highest in Kigali (44%) and lowest in Butare (11%). Cutting infection resulting from the use of CMD-affected planting material was the main type of infection. Disease symptoms were generally severe, with little difference between cultivars or locations. Most affected plants lacked the ‘candle-stick’ symptoms characteristic of severe CMD associated with infection by the ‘Uganda Variant’ of East African cassava mosaic virus (EACMV-UG2). PCR analysis detected two viruses in CMD-affected plants: African cassava mosaic virus (ACMV) and EACMV-UG2. ACMV predominated and occurred throughout the surveyed areas, whereas EACMV-UG2 was restricted to the prefectures of Byumba, which border south-western Uganda and Kibungo in south-eastern Rwanda. No dual infections were detected.